Analogue and digital signal processing circuits for hearing instruments - Tan, Meng Tong. (2008)
We describe in this thesis the analysis, design and IC implementation of analogue and digital signal processing circuits for low voltage (1.1 – 1.4V) low power (10s-100?A) applications, including hearing instruments. Our research includes theoretical and practical aspects.